Playing-on-Words as a Strategy of Making Famous Comic TV Shows: Mind Your Language as a Sample - Fayadh, Ahlam Abid; Mohammed, Walaꞌa Hashim (Al-Adab Journal, 2019)
Wordplay is created by exploiting features of languages and depending on ambiguity of meaning. This research tries to investigate two main goals, one general and another specific. The general goal is to investigate how playing-on-words is created in TV-shows and how it contributes differently in making different sorts of comic shows. The specific goal, on the other hand, is to investigate the use of this linguistic phenomenon in a famous comic TV show named Mind Your Language.Mind Your language is analyzed following Delabastita (1996) and Bloomfield's (2007) models of forms and functions of wordplay respectively. For the aim of figuring out the general goal, the research refers to a previous study made on the use of wordplay in an animated comic show named The Simpsons and discusses the difference between the two, concerning show type and the way wordplay contributes in each.The research concludes the following: (i) playing-on-words is an essential strategy for comic TV show making and it contributes differently in different shows ,(ii) almost all forms of wordplay are used in Mind Your Language,(iii)sometimes an intended move is required in words/expressions to make them work and create a wordplay such as an intended mispronunciation to form homophones, (iv) an instance of wordplay can serve more than one function and telling jokes is the main function that all of them serve in comic TV shows, (v) and finally a playing-on-words can serve an educational function, that is, it can be a good way to spread language knowledge.